The HD 260655 system: Two rocky worlds transiting a bright M dwarf at 10 pc - Luque, Rafael; Molaverdikhani, Karan; Kemmer, Jonas; Khalafinejad, Sara; Kossakowski, Diana; Quirrenbach, Andreas; Reffert, Sabine; Stock, Stephan; Trifonov, Trifon (Astronomy and astrophysics, 2022)
We report the discovery of a multiplanetary system transiting the M0 V dwarf HD 260655 (GJ 239, TOI-4599). The system consists of at least two transiting planets, namely HD 260655 b, with a period of 2.77 d, a radius of Rb = 1.240 ± 0.023 R⊕, a mass of Mb = 2.14 ± 0.34 M⊕, and a bulk density of ρb = 6.2 ± 1.0 g cm−3, and HD 260655 c, with a period of 5.71 d, a radius of , a mass of Mc = 3.09 ± 0.48 M⊕, and a bulk density of g cm−3. The planets have been detected in transit by the Transiting Exoplanet Survey Satellite (TESS) mission and confirmed independently with archival and new precise radial velocities obtained with the HIRES and CARMENES instruments since 1998 and 2016, respectively. At a distance of 10 pc, HD 260655 has become the fourth closest known multitransiting planet system after HD 219134, LTT 1445 A, and AU Mic. Due to the apparent brightness of the host star (J = 6.7 mag), both planets are among the most suitable rocky worlds known today for atmospheric studies with the James Webb Space Telescope, both in transmission and emission.